Dimensionless Assessment Method of Landslide Dam Formation Caused by Tributary Debris Flow Events - Kun-Ting Chen; Xiao-Qing Chen; Gui-Sheng Hu; Yu-Shu Kuo; Yan-Rong Huang; Chjeng-Lun Shieh (Geofluids)
In this study, we develop a dimensionless assessment method to evaluate landslide dam formation by considering the relationship between the run-out distance of a tributary debris flow and the width of the main stream, deposition thickness of the tributary debris flow, and the water depth of the main stream. Based on the theory of debris flow run-out distance and fan formation, landslide dam formation may result from a tributary debris flow as a result of two concurrent formation processes: (1) the run-out distance of the tributary debris flow must be greater than the width of the main stream, and (2) the minimum deposition thickness of the tributary debris flow must be higher than the in situ water depth of the main stream. At the confluence, one of four types of depositional scenarios may result: (1) the tributary debris flow enters into the main stream and forms a landslide dam; (2) the tributary debris flow enters into the main stream but overflow occurs, thus preventing complete blockage of the main stream; (3) the tributary debris flow enters into the main stream, does not reach the far bank, and sediment remains partially above the water elevation of the main stream; or (4) the tributary debris flow enters into the main stream, does not reach the far bank, and sediment is fully submerged in the main stream. This method was applied to the analysis of 11 tributary debris flow events during Typhoon Morakot, and the results indicate that the dimensionless assessment method can be used to estimate potential areas of landslide dam formation caused by tributary debris flows. Based on this method, government authorities can determine potential areas of landslide dam formation caused by debris flows and mitigate possible disasters accordingly through a properly prepared response plan, especially for early identification.